Broadband MoS2 Field‐Effect Phototransistors: Ultrasensitive Visible‐Light Photoresponse and Negative Infrared Photoresponse - Wu, Jing‐Yuan; Chun, Young Tea; Li, Shunpu; Zhang, Tong; Wang, Junzhan; Shrestha, Pawan Kumar; Chu, Daping (Advanced materials (Weinheim), 2018)
Inverse photoresponse is discovered from phototransistors based on molybdenum disulfide (MoS2). The devices are capable of detecting photons with energy below the bandgap of MoS2. Under the illumination of near‐infrared (NIR) light at 980 and 1550 nm, negative photoresponses with short response time (50 ms) are observed for the first time. Upon visible‐light illumination, the phototransistors exhibit positive photoresponse with ultrahigh responsivity on the order of 104–105 A W−1 owing to the photogating effect and charge trapping mechanism. Besides, the phototransistors can detect a weak visible‐light signal with effective optical power as low as 17 picowatts (pW). A thermally induced photoresponse mechanism, the bolometric effect, is proposed as the cause of the negative photocurrent in the NIR regime. The thermal energy of the NIR radiation is transferred to the MoS2 crystal lattice, inducing lattice heating and resistance increase. This model is experimentally confirmed by low‐temperature electrical measurements. The bolometric coefficient calculated from the measured transport current change with temperature is −33 nA K−1. These findings offer a new approach to develop sub‐bandgap photodetectors and other novel optoelectronic devices based on 2D layered materials. Broadband phototransistors based on molybdenum disulfide (MoS2) with inverse photoresponse are reported. At 454 nm, the phototransistors exhibit ultrahigh photoresponsivity on the order of 104–105 A W−1. While upon near‐infrared light illumination, negative photoresponses with fast response time (50 ms) are observed for the first time. This work offers a new approach to developing sub‐bandgap photodetectors and other novel optoelectronic devices.